Nanotube formation favored by chalcogen-chalcogen interactions - Werz, Daniel B.; Gleiter, Rolf; Rominger, Frank (Journal of the American Chemical Society, 2002)
Close contacts between sulfur, selenium, and tellurium centers are used to construct nanotubes in the solid state which are able to host other molecules.
Gesehen am 03.11.2020